(untitled) (Herald of Journalism, 2018)
The press is not only a source of information – reflection of existence, functioning of language, and also means of formation of the correct Kazakh speech and writing. The press occupies a special role in formation of special words, terms in the sphere of science and technics and industry. It served as the reason of our attempt in this article to consider functions of the press in formation of the Kazakh terminology. In this regard newspapers starting with the first Kazakh newspapers to today’s were the object of the research. The newspapers of the different periods and terms used in them were considered separately. It was revealed, what methods and techniques were used in formation of the terms on pages of newspapers of tecent years. In the article it was mentioned about the terms formed according to our sound features and the ones not translated into the national language yet. And also the mistakes made in the course of formation of terms on the pages of the press were defined. Key words: term, terminology, the issue of terminology, Kazakh press, newspaper, term formation.